Competências para o desenvolvimento docente na educação interprofissional em saúde - Leite, Daniella Rosaly (Universidade Federal de São Carlos, 2024)
Interprofessional education (IPE) is recognized as an innovative strategy capable of supporting, through its theoretical-conceptual and methodological frameworks, the necessary transformations in professional education and health work. The success of any educational action in IPE depends on the teacher’s ability to mobilize facilitation skills. However, the challenge lies in the absence of a set of competencies that globally underpin actions for faculty development (FD) in interprofessional education. Methodology: Descriptive-exploratory research with a qualitative approach, whose data collection took place in three stages. The first stage consisted of a scoping review and then a thematic content analysis. The second and third stages were collected using the Delphi method, with the participation of IPE specialists from the Brazilian national scene, and analyzed according to consensus and the content validity index (CVI). Results: In the first stage, two themes emerged: 1. Collaborative and facilitation competencies for IPE; 2. Competencies for FD in IPE. In the second stage, seven experts analyzed four competencies with consensus ≥ 80% in two rounds. In the third stage, ten experts analyzed four competences organized into domains, definitions and actions, with consensus ≥ 80% with two rounds. The final competency framework consisted of four competencies validated by the experts: 1. understanding of the socio-historical-cultural aspects of IPE and interprofessional collaborative practice (ICP) in the context of health needs, users, and health systems; 2. elaboration of the learning objectives and expected results of IPE proposals with the explicit intention of developing collaborative competencies; 3. systematization of the theoretical and methodological assumptions of IPE and ICP; 4. Application of teaching-learning methods and the evaluation process from an interactive and shared perspective to operationalize interprofessional education. Final considerations: The validated competency framework is a tool that will allow IPE facilitators to improve and institutionalize IPE in different contexts and practices, contributing to the progress of FD initiatives in IPE and to the curricular implementation of IPE in different locations.
Competencies for faculty development in interprofessional health education
Keywords: Docentes; Teachers; Competência; Competence; Desenvolvimento docente; Faculty development; Educação interprofissional em saúde; Interprofessional health education; CIENCIAS DA SAUDE